2021
DOI: 10.3390/plants10102136
|View full text |Cite
|
Sign up to set email alerts
|

The Physiological and Biochemical Responses of European Chestnut (Castanea sativa L.) to Blight Fungus (Cryphonectria parasitica (Murill) Barr)

Abstract: The most important disease of European chestnut (Castanea sativa Mill.) is chestnut blight caused by the fungus Cryphonectria parasitica (Murrill) Barr which induces yield reduction in Europe and North America. This study aimed to investigate the impacts of C. parasitica infection on the physiological and biochemical characteristics of European chestnut at two different growth stages, 3 and 6 weeks after the infection. The amount of photosynthetic pigments (chlorophyll-a, chlorophyll-b, and carotenoids), the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The Cucumber Green Mottle Mosaic Virus infection induced higher APX, POX, and SOD activities in cucumber plants [ 84 ]. The results of Kovács et al [ 85 ] showed higher APX, POX, and SOD activities in European chestnut leaves infected with Cryphonectria parasitica . Barley plants infected with Blumeria graminis f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…The Cucumber Green Mottle Mosaic Virus infection induced higher APX, POX, and SOD activities in cucumber plants [ 84 ]. The results of Kovács et al [ 85 ] showed higher APX, POX, and SOD activities in European chestnut leaves infected with Cryphonectria parasitica . Barley plants infected with Blumeria graminis f. sp.…”
Section: Discussionmentioning
confidence: 99%
“…A previous explanation for this limited success is the complex structure of VCGs among C. parasitica strains in North America, which restricts CHV1 horizontal transmission. Previous studies have shown that C. parasitica infection increases proline production in chestnuts 65 , and that CHV1 transmission rates are higher in planta than in vitro 21,38,[66][67][68] . Therefore, we hypothesize that the enhanced transmission of CHV1 in chestnuts is mediated by plant proline, similarly to transmission of HAVs in S. sclerotiorum.…”
Section: G Protein Signaling Pathwaymentioning
confidence: 92%
“…(a) Determination of SOD activity: SOD activity was determined using the NBT photoreduction method [50]. Absorbance at 560 nm was measured using a spectrophotometer, and the specific activity was calculated based on the 50% inhibition of NBT photoreduction.…”
Section: Effect Of Mycotoxin On Plant Enzyme Activitiesmentioning
confidence: 99%